Methods of digital protection of graphic images - Shabala, Eugene; Latanskaya, Anastasia (Transfer of innovative technologies, 2021)
The rapid development, widespread use of information and communication technologies in our time, the ease of transmission and dissemination of information in computer networks entail the need to protect files published in the public domain or documents transmitted over the network. Ensuring reliable transmission and storage of information involves two aspects: first, the prevention of unauthorized access to data and, secondly, ensuring reliable data transmission despite obstacles.